The Analysis Study of Efficacy and Effectiveness of Laser and Light Therapy for The Treatment of Cutaneous Disorders of Hyperpigmentation : A Comprehensive Systematic Review - Putri, Putu Mahadevy Pradnyandhari; Savitri, I Dewa Ayu Agung Ananda (The International Journal of Medical Science and Health Research, 2024)
Background: Hyperpigmentation, which happens when a skin region is darker than its surroundings, is typical in people with dark skin tones. In these subjects more than in lighter-toned ones, hyperpigmentation usually lasts longer and is harder to treat. The aim: The aim of this study to show about efficacy and effectiveness of laser and light therapy for the treatment of cutaneous disorders of hyperpigmentation. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Sciencedirect were used to do this. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Highlighting Q-Switched laser treatments as the gold standard for hyperpigmentations. In our cohort of patients, lighter phototypes, lesions located on the trunk or limbs, and superficial melanosis better responded to the treatment.